Japanese Outbound Market to Singapore - Aw, Yeow Keng (2007)
This research examines Japanese tourists' perceptions of Image of Singapore and attempts to apply motivational theories to attract Japanese tourists not only to come but stay longer in Singapore. For the analysis, data were collected via a questionnaires-based survey among the 650 Japanese tourists at Singapore Changi Airport, Departure Hall. The purpose of survey is to find out Japanese tourists' perceptions of Singapore as a travel destination, their satisfactions toward Singapore and likelihood of them to recommend the Singapore to others. Overall, the result of survey is positive.